The Well-Being Impacts Associated with College in Prison: A Comparison of Incarcerated and Non-Incarcerated Students Who Identify as Women - Moore, Sarah Y. (The prison journal, 2023)
Benefits of college in prison (CIP) programs often center on reduced recidivism and other post-release adjustment outcomes. This article argues for broader recognition of positive outcomes to include well-being, coping, and academic engagement for incarcerated students, noting the specific challenges for female-identifying inmates with backgrounds that often include high levels of abuse and violence. Using longitudinal data from female-identifying students in a CIP program and comparison data from a matched non-incarcerated sample, improvements in these outcome measures are demonstrated as incarcerated students remain in the program. Importantly, their measures of well-being, coping, and academic engagement were significantly better than the matched non-incarcerated sample for most measures. Further, the possible underlying mechanism for the findings is discussed, linking them to program characteristics that emphasize the development of community, agency, and personalized—in-person education—qualities that are in alignment with trauma-informed practices.